Deformation of Steel Slag Asphalt Mixtures Under Normal Temperature Water Immersion - Wang, Chao; Zhang, Caili (Frontiers in Materials, 2021)
To study the deformation resistance of steel slag asphalt mixtures (SSAMs) under rainy conditions, limestone–asphalt mixtures (LAMs) and SSAM were soaked in water at room temperature for 120 days and rutting tests and triaxial compression tests were carried out. The results show that the deformation resistance of SSAM was improved after 120 days of immersion, the cohesion did not decrease significantly, and the internal friction angle increased by 25.1%; the deformation resistance of LAM decreased significantly, the cohesion decreased by 27.1%, and the internal friction angle decreased by 21.1%. To better understand the reason for the increased anti-deformation ability, adhesion tests of asphalt and microscopic studies of the steel slag surface were performed. The experimental results showed that the cohesion of steel slag did not decrease significantly after immersion because of the excellent adhesion between steel slag and asphalt. The increased internal friction angle was caused by calcium hydroxide and other crystals formed on the surface of the steel slag mixture after immersion, which increased the surface roughness of the steel slag aggregates and the internal friction angle of the SSAM. The mechanical properties of semirigid asphalt pavement were analyzed by ANSYS. It was determined that the shear stress of this type of pavement is large, and it can easily produce permanent deformations. Under the influence of moisture, the anti-deformation ability of SSAMs can grow, which promotes the high-temperature deformation resistance of asphalt pavement. Based on a test road used for 2 years, the SSAM pavement exhibited no pavement problems, such as cracking, loosening, or rutting, which indicates good practical road performance.